Targeted tumor MRI with gadobutrol-loaded anti-HER2 immunoliposomes. (May 2017) - Chen, Weicui; Liu, Bo; Chen, Jun; Liu, Guoqing; Liu, Xian
Background: Immunoliposomes have been used to deliver MR contrast agents to cancer tissue by targeting tumor associated antigens, thus enabling the visualization of biological processes at the cellular level. Purpose: To develop and evaluate the feasibility of specific HER2 targeted liposomal MR contrast agent. Material and Methods: Gd-loaded anti-HER2 immunolipomes (Gd-ILs) and non-targeted PEGylated liposomes (Gd-NTLs) were prepared and characterized. Tumor bearing animals were randomized into three groups: Gd- ILs, Gd- NTLs and gadobutrol. Animals were imaged prior and 5, 15, 60, 120 and 180 min after i.v. injection of different contrast agents. The signal intensity enhancement percentage, signal- to- noise ratio and contrast- to –noise ratio was used to qualify tumor enhancement of different groups. After imaging, tumors were excised for histological examination. Results: In vivo dynamic MR images, the specific targeted contrast agent bound to tumor tissue and result in a gradual and persisting enhancement for at least 3 hours in mice bearing tumor xenografts, reaching a maximum of 87.7% enhancement after 120 min post-injection. Gd-ILs demonstrated superior tumor enhancement over control non target contrast agent and gadobutrol in HER2 overexpressing tumors at 60, 120 and 180 min post- injection. The SNR and CNR of Gd-ILs in the tumors were significantly greater than that of Gd-NTLs at 60, 120, 180 min post- injection. Conclusion: The results indicate the feasibility of Gd-ILs providing prolonged circulation, specific tumor enhancement and cancer cell recognition as targeted contrast agent.